2005
DOI: 10.1007/s00018-005-5226-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by transmembrane peptides of chimeric insulin receptors

Abstract: Receptor tyrosine kinases play essential roles in cell proliferation and differentiation. We have recently shown that peptides corresponding to the transmembrane domains of the epidermal growth factor (EGF) and ErbB2 receptors inhibit their corresponding receptor activation in cancer cell lines. We extend this observation to cells transfected with chimeric insulin receptors where the transmembrane domain has been replaced by that of the EGF receptor or a mutated Erb2 domain. Peptides corresponding to the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 20 publications
2
37
0
Order By: Relevance
“…Such a motif has been shown to be important for the dimerization of TM segments of ErbB receptors (Mendrola et al, 2002). Consistently with previous work by Marchesi and colleagues (Bormann et al, 1989), we have also recently demonstrated that synthetic peptides mimicking TM domains are able to inhibit specifically kinase activity and cell signaling by EGF (erbB1) and erbB2 receptors in cultured cells (Bennasroune et al, 2004) as well as chimeric insulin receptors containing these domains (Bennasroune et al, 2005). This inhibition indeed relates to the presence of the GxxxG-type sequence.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…Such a motif has been shown to be important for the dimerization of TM segments of ErbB receptors (Mendrola et al, 2002). Consistently with previous work by Marchesi and colleagues (Bormann et al, 1989), we have also recently demonstrated that synthetic peptides mimicking TM domains are able to inhibit specifically kinase activity and cell signaling by EGF (erbB1) and erbB2 receptors in cultured cells (Bennasroune et al, 2004) as well as chimeric insulin receptors containing these domains (Bennasroune et al, 2005). This inhibition indeed relates to the presence of the GxxxG-type sequence.…”
Section: Introductionsupporting
confidence: 91%
“…When TM domain interactions induced dimerization of this fusion protein, the reporter gene was activated. Here, we used a modified version in which the reporter gene encodes for the luciferase protein (Bennasroune et al, 2005). TM domains of NRP1, mutated NRP1, ErbB2, GPA, and mutated GPA were used for fusion protein construction.…”
Section: Estimation Of Tm-nrp1 Dimerization (Toxluc Method)mentioning
confidence: 99%
See 2 more Smart Citations
“…TM-I peptide consisted of residues 37-62 (VITSLLLGTLIFCAVLGNACVVAAIA); TM-II peptide of residues 74 -98 (LIGSLAVTDLMVSVLVLPMAALYQ V); TM-III peptide of residues 110 -132 (DLFIALDVLCCTSSILHLCAIA L); TM-IV peptide of residues 153-178 (AAALISLTWLIGFLISIPPMLG WRTP); TM-V peptide of residues 192-217 (DHGYTIYSTFGAFYIPLLL MLVLYGR); TM-VI peptide of residues 346 -367 (TLGIIMGTFILCWL PFFIVALV); and TM-VII peptide of residues 379 -403 (TLLGAIINWL GYSNSLLNPVIYAYF). At the C-terminal juxtamembrane sequence of each TM peptide was introduced the tribasic sequence (RKR) as found in many membrane proteins to reduce possible artifact formation through disulfide bridges and to ensure incorporation into the plasma membrane of cells, as has been demonstrated previously (Bennasroune et al, 2004(Bennasroune et al, , 2005. Immediately before use, the peptides were solubilized in dimethyl sulfoxide (DMSO) and diluted in the corresponding cell culture medium to yield a final concentration of 1% DMSO.…”
Section: Chemicals Reagents and Drug Administration (S)-mentioning
confidence: 99%